PELATIHAN SERVICE EXCELLENT PADA KSP “AR ROHMAH” JAWA TIMUR MENUJU KONVERSI SYARIAH - Renny Oktafia; Mentari Clara Dewanti (CV. Manha Digital, 2023)
Community Service is carried out by providing Service Excellent improvement training to employees of the “Ar Rohmah” Savings and Loans Cooperative (KSP), Candi, Sidoarjo. Where, currently it is in the transition period to become a Sharia KSP. The implementation of the training is divided into several parts, namely, the introduction of sharia cooperatives and an overview of the duties of each administrator and excellent service. This training is expected that the participants can understand the training activities provided and can help the cooperative in managing sharia-based HR performance properly and experiencing improvement. So that the process of transition to sharia can run according to the provisions. The results show that there has been a significant increase, related to the ability of KSP